Zagadnienie Osobliwe w Płaskim Ośrodku z Naprężeniami Momentowymi - Ganowicz, R. (Engineering Transactions, 1970)
In this paper the solution in the form of closed expressions are given for a plane infinite medium with moment stresses successively under a concentrated load and subjected to the action of a compressing centre. The solutions were obtained following the introduction of two functions of displacements into the considerations, and with the application of the double infinite Fourier’s transform.